Patients crash more than airlines: a medical emergency at 35,000 ft - Talha Bashir (Greater Baltimore Medical Center, 2014)
An estimated 1 in 600 commercial flights will have an onboard medical emergency and approximately half of the time a passenger physician will provide medical assistance. A medical emergency on an aircraft can be a daunting task for even the most seasoned physician. This article is a narrative case report from a physician passenger who found himself in the midst of such an emergency on a 15-hour international flight.